Analisis Konflik Pengaturan Tindak Pidana Penggelapan Objek Fidusia dalam UU Fidusia dan KUHP - Ali Yusran Gea (Jurnal Hukum Lex Generalis, 2025)
This research discusses the existence of embezzlement crimes against fiduciary collateral objects based on Law Number 42 of 1999 and its comparison with Article 372 of the Criminal Code. In practice, the transfer of fiduciary collateral objects often occurs due to economic pressures, a lack of legal understanding, and the assumption that fiduciary is only a civil matter. In fact, the Fiduciary Law contains criminal provisions in Article 36. This study highlights the dualism of legal regulation that creates legal uncertainty. This research aims to analyze the clarity of norms and legal protection for creditors through a normative legal approach based on Indonesian positive law.